Management Model of Hizbul Wathan Extracurricular Development in Muhammadiyah Senior High School - et. al., Endang Listiowaty, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the management development of Hizbul Wathan's extracurricular coaching model to improve Muhammadiyah students' competence in Indonesia. This qualitative research involved 6 participants who represented each data variable. Methods of data collection by observation, interviews, documentation. Data analysis used an interactive model from Milles and Huberman. The study results found that the Scout Movement of Hizbul Wathan has been carried out to manage Human Resources by involving administrators from the Central Quartir to the Branch Quartirs and coaches in Qabilah throughout Indonesia. Organisation and network management to lay a solid foundation for improving students' quality as Muslim is emphasised.